Absinthe & flamethrowers [ projects and ruminations on the art of living dangerously - Gurstelle, William (Chicago Review Press, 2009)
Suitable for reasonable risk takers and suburban dads who want to add more excitement to their lives, this title offers a combination of science, history, and DIY projects that explains why danger is good for you and details the art of living dangerously.